Regioselective synthesis of novel spiro-isoxazolines congeners as antimicrobial agents: in vitro and in-silico assessments - Bouzammit, Rachid; Ait Assou, Soumia; Er-Rajy, Mohammed; Aflak, Noura; Bahsis, Lahoucine; Chalkha, Mohammed; El Hassouni, Mohammed; Lachkar, Mohammed; Ben Hadda, Taibi; Benson, Daryn; Alyousef, Abdullah A.; Aboul-Soud, Mourad A. M.; et al. (Frontiers in Chemistry, 2025)
IntroductionA new class of spiroisoxazolines was efficiently synthesized through a regioselective cycloaddition between arylidene tetralone 1 and arylnitrile oxides 2, characterized and assessed for their in vitro antimicrobial activity.MethodsThe structures and regioselectivity of the obtained cycloadducts were confirmed by 1H, 13C-NMR, IR, elemental analysis, and mass spectrometry, and further supported by theoretical calculations that explained the reaction process and the regioselective results. The antimicrobial profile of the synthetized spiro derivatives was evaluated against the yeast Candida albicans, the Gram-postive bacteria (Staphylococcus aureus and Bacillus subtilis), and the Gram-negative bacteria (Escherichia coli and Pectobacterium basiliensis). In addition, in silico studies were carried out to rationalize the experimental findings and provide mechanistic insight.Results and DiscussionTwo spiroisoxazolines, defined as 3b and c, showed notable antimicrobial activity, producing inhibition zones between 8.33 ± 0.57 and 14.00 ± 2.00 mm. Compound 3b was active against all tested strains and demonstrated ampicillin-comparable MIC values of 10 μg/mL against E. coli, P. brasiliensis, and B. subtilis. It showed moderate to weak activity against S. aureus (90 μg/mL) and C. albicans (300 μg/mL). Compound 3c displayed selective activity toward Gram-positive bacteria with MIC values of 50 and 500 μg/mL against B. subtilis and S. aureus, respectively. Molecular docking studies confirmed the high binding affinities of 3b and 3c toward the active sites of the targeted proteins, in agreement with the antimicrobial results. POM analyses further indicated the coexistence of antifungal (O1δ−—O2δ−) and antiviral (O1δ−—N1δ−) pharmacophoric sites, although steric constraints introduced by two methyl substituents may limit their optimal interaction. The calculations also confirmed favorable bioavailability and the absence of predicted toxicity for all compounds. Overall, this combined experimental -theoretical study highlights the mechanistic basis and biological relevance of these spiroisoxazolines, underscoring their potential as promising scaffolds for the rational design of antiviral drug candidates.